Rail Electronic Data Interchange in a Border Crossing Point in South East Europe : An Assessment of Options - World Bank (Washington, DC, 2015)
Within the European Union (EU) rail transport is currently the least integrated transport mode. This leads to delays, extra costs, and insufficient use of rail freight, especially for time-sensitive cargo. This also represents a missed opportunity in terms of moving towards a greener transport modal split within the EU. Rail freight, for which international activity represents 50 percent of total activities, will not be able to develop fully if border crossing rail operations do not deliver a better service for shippers and freight operators who require seamless trans-national transport as is possible by road, air and sea. Observing that the modal split of rail in the EU is stagnating at around 16 percent after years of decline, the European Commission proposed a regulation on a European rail network for competitive freight to be based on a number of rail freight corridors which entered into force on November 9, 2010. Regulation No 913/2010 makes it mandatory to create a European rail network for competitive freight based on international freight corridors, recognizing that the need to strengthen the competitiveness of rail freight requires a corridor approach, involving corridors that cross national borders. TheEU adoption in 2010 of a corridor approach focusing on international rail freight has important implications for EU member states, accession and candidate countries, in terms of approaching rail freight investments and performance from an international corridor perspective with enhanced cross-border coordination, with the ultimate aim of increasing the attractiveness of rail to potential freight customers. The objective of this report is to address this recommendation by assessing whether it makes sense to introduce a pilot EDI in a rail border crossing point in South East Europe. It aims to make a preliminary assessment of the various technical options in terms of hardware, software, and communication requirements of such architecture, taking into account that any technical solution proposed needs to be adapted to the countries in question, given existing infrastructure and European regulations. The ultimate aim is to improve rail border crossing performance in South East Europe by the use of EDI to improve integration.